2021
DOI: 10.1111/psq.12710
|View full text |Cite
|
Sign up to set email alerts
|

Polls and Elections Accuracy and Bias in the 2020 U.S. General Election Polls

Abstract: AUTHOR'S NOTE: Kyle Endres and I conducted a preliminary analysis of the final, national, presidential preelection polls in 2020 (Panagopoulos and Endres 2020). I am grateful to Kyle for his collaboration support for the current, expanded study, which benefited enormously from his generous assistance, including some additional data collection and initial analyses. The author is solely responsible for the calculations, interpretations, and conclusions reported in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Our results therefore point to a systematic bias in US pre-election polls that affects not only Trumpists but all Republican candidates who have run in recent contests. 1,3,5,9 Thus, whatever Trump has in common with the candidates he has endorsed, these characteristics do not appear to explain why support for Republican candidates has been underestimated by pre-election polls.…”
Section: What Are the Implications Of Our Results?mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results therefore point to a systematic bias in US pre-election polls that affects not only Trumpists but all Republican candidates who have run in recent contests. 1,3,5,9 Thus, whatever Trump has in common with the candidates he has endorsed, these characteristics do not appear to explain why support for Republican candidates has been underestimated by pre-election polls.…”
Section: What Are the Implications Of Our Results?mentioning
confidence: 99%
“…They found that Trump was no more underestimated by the polls than any other Republican candidate 1 . After the 2020 US presidential election, this general Republican bias was even more pronounced: when examining pre‐election polls for the presidential, senatorial, and gubernatorial elections, not only was Trump substantially underestimated, but so were all Republican candidates – even those who were very different to Trump 5 …”
Section: The “Shy Trump” Theory and Unlikely Votersmentioning
confidence: 99%
“…One of the most widely used measures asks respondents whom they plan to vote for. This question, or some flavor of it, is valuable in predicting the outcome of elections (though less so recently; see Panagopoulos, 2021). These types of measures, as valuable as they are, also come with limitations, namely, in their inability to access unprimed voters' opinions of the candidate or if the candidate is their actual preference versus a conditional preference.…”
Section: Traditional Measures Of Candidate Approvalmentioning
confidence: 99%
“…However, this assumption does not hold when nonresponse is correlated with the variable of interest. Such survey bias may explain some of the 2020 preelection polling misses (Clinton et al 2021; Keeter, Kennedy, and Deane 2020; Panagopoulos 2021).…”
Section: Declining Response Rate and Survey Biasmentioning
confidence: 99%